Surasundaris on the base of the pillar of the Mukhamandapa - Temples of India Project Team (Jio Institute, 2024)
A closer view of the sculptures on the base of the pillar of the mukhamandapa (front porch). These sculptures are mostly of surasundaris (celestial damsels). The base of the pillar has mouldings that resemble the kumbha (pot), kalasha (a pitcher), and kapotali (cyma recta) mouldings in a temple plinth.